Digital Technology in Environmental Education Adiwiyata Program for Elementary School Children in Facing Climate Change in Samarinda City (Open Society Conference, 2025)
This research investigates the effectiveness of integrating digital technology into environmental education within the Adiwiyata Program at elementary schools in Samarinda. The study employs a literature review approach, meticulously analyzing a range of academic sources, policies, and local documentation to assess the impact of this integration. The results demonstrate that digital tools, including e-modules, educational videos, and interactive simulations, successfully improve students' environmental literacy and critical thinking skills related to climate change issues. Furthermore, the study highlights the strategic importance of teachers as learning facilitators who design action-oriented experiences. The involvement of parents and the wider school community, supported by digital platforms, also plays a significant role in promoting sustainability values. Despite these positive outcomes, the research identifies notable barriers, such as inadequate ICT infrastructure and the need for enhanced digital competency among teachers.bThe findings lead to several key recommendations, including the necessity for ongoing training, better access to digital educational resources, and fostering closer collaborations between schools and their communities. Theoretically, the study supports the principles of ecopedagogy and systems thinking. This work is intended to serve as a practical and theoretical basis for developing innovative and sustainable digital learning models.